Nursing of a patient with gout of damp-heat stagnation syndrome combined with erosive gastritis treated with auricular acupoint therapy combine with pricking and cupping therapy (耳穴疗法联合刺络拔罐治疗湿热蕴结证痛风伴糜烂性胃炎1护理体会) - ZHU Jianmei (朱建妹); CHEN Hui (陈慧); ZHANG Xiaolin (张小林); LIAO Xuefeng (廖雪锋) (中西医结合护理)
This paper summarizes nursing measures for a patient with gout of damp-heat stagnation syndrome combined with erosive gastritis treated with auricular acupoint combine with pricking and cupping therapy. In addition to routine nursing, individualized auricular acupoint treatment including auricular bloodletting and pressing combined with pricking and cupping therapy were carried out, aiming at relieving heat and detoxification at early stage of disease, promoting blood circulation, dredging collaterals and regulating qi at midterm and invigorating spleen and warming kidney Yang and end stage of treatment. The combined treatment using Traditional Chinese medicine technology is effective to relieve the pain, reduce the joint swelling, and improve the recovery of joint movement, as well as protecting the gastric mucosa of the patient. (本文总结耳穴疗法联合刺络拔罐治疗1例痛风伴糜烂性胃炎的护理经验。在常规护理基础上, 通过制定个体化的耳穴疗法(包括耳穴放血和耳穴压豆)和刺络拔罐治疗, 基于早期泄热排毒, 中期活血散瘀通络疏肝理气, 后期健脾益气、温补肾阳的思路, 以达到即时止痛、快速消除关节肿胀、恢复关节活动功能及保护胃黏膜的效果。)